Peranan Orang Tua Pada Pembinaan Iman Anak Usia 1-5 Tahun Melalui Tradisi Tandak Timang Di Desa Batu Badinding Kecamatan Katingan Tengah - Lidia Selfitri; Eva Inriani; Prasetiawati Prasetiawati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The Tandak Timang tradition in Batu Badinding Village, Central Katingan District, plays an important role in fostering the faith of children aged 1-5 years, which is carried out by parents. From an early age, children are introduced to faith values through Tandak Timang verses that contain advice, prayers, and praise to God. This study aims to (1) describe the role of parents in fostering the faith of children aged 1-5 years through the Tandak Timang tradition in Batu Badinding Village, Central Katingan District; and (2) describe the values implemented by parents for children aged 1-5 years in Batu Badinding Village, Central Katingan District. The research used a qualitative descriptive method with data collection techniques including observation, interviews, and documentation.The results show that Tandak Timang plays a significant role in shaping children's spiritual foundation. Parents' roles are manifested through daily practices, such as singing, storytelling, and rocking children while chanting verses in the Dayak Ngaju language. This practice not only builds strong emotional bonds but also serves as an effective medium for instilling noble values. These values include cultural values, moral and ethical values, ancestral values, and spiritual values that teach children about the importance of prayer and hope in God.The conclusion of this study is that parents act not only as cultural inheritors but also as educators, role models, and facilitators. They utilize intimate moments when putting children to sleep—through singing, storytelling, and rocking—to instill faith values. The strong physical and emotional interaction builds a solid bond, making it easier for children to accept and internalize a deep understanding of the teachings conveyed. The Tandak Timang tradition is rich in noble values that serve as the foundation for faith formation. These values include cultural values, moral and ethical values, ancestral values, and spiritual values. The suggestions put forward are that parents should further understand the meaning of Tandak Timang for fostering children's faith from an early age, and pass on and preserve the character of children through this Central Kalimantan Dayak culture. For subsequent researchers conducting similar studies, it is recommended to develop the research objectives and focus more specifically on the research topics.